2013
DOI: 10.1016/j.ydbio.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The Xin repeat-containing protein, mXinβ, initiates the maturation of the intercalated discs during postnatal heart development

Abstract: The intercalated disc (ICD) is a unique structure to the heart and plays vital roles in communication and signaling among cardiomyocytes. ICDs are formed and matured during postnatal development through a profound redistribution of the intercellular junctions, as well as recruitment and assembly of more than 200 proteins at the termini of cardiomyocytes. The molecular mechanism underlying this process is not completely understood. The mouse orthologs (mXinα and mXinβ) of human cardiomyopathy-associated (CMYA)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 44 publications
5
42
0
Order By: Relevance
“…week postnatal, upregulated mXin␤ colocalized with N-cadherin puncta to form bigger aggregates along the developing intercalated discs between cardiomyocytes (60). In this regard, we also observed similar mXin␤ aggregates along the MTJ of mXin␣-null muscles (data not shown), suggesting an analogous mechanism for the MTJ formation.…”
Section: Discussionsupporting
confidence: 69%
“…week postnatal, upregulated mXin␤ colocalized with N-cadherin puncta to form bigger aggregates along the developing intercalated discs between cardiomyocytes (60). In this regard, we also observed similar mXin␤ aggregates along the MTJ of mXin␣-null muscles (data not shown), suggesting an analogous mechanism for the MTJ formation.…”
Section: Discussionsupporting
confidence: 69%
“…XIRPs interact with catenins and ion channels in mature cardiac muscle and, although the significance of phosphorylation is unclear, gene knockout mice display early-onset cardiomyopathy (18).…”
Section: Resultsmentioning
confidence: 99%
“…Because previous studies have reported that XIRP2 is specific for cardiac and skeletal muscle (Huang et al, 2006; Q. Wang et al, 2012), our discovery of XIRP2 in sensory hair cells came as a surprise. The genetic locus of the Xirp2 gene overlaps with two unresolved human deafness loci (DFNB27 and DFNA16;Fukushima et al, 1999;Pulleyn et al, 2000), making its study significant for deafness research.…”
Section: Introductionmentioning
confidence: 90%
“…Complete loss of XIRP2 causes diastolic dysfunction and early postnatal mortality in mice (Q. Wang et al, 2010), suggesting that it might play a role in the development and maturation of the intercalated disks (Q. Wang et al, 2010Wang et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation